A comprehensive overview of directing groups applied in metal-catalysed C–H functionalisation chemistry12. (23rd July 2018) - Sambiagio, Carlo; Schönbauer, David; Blieck, Remi; Dao-Huy, Toan; Pototschnig, Gerit; Schaaf, Patricia; Wiesinger, Thomas; Zia, Muhammad Farooq; Wencel-Delord, Joanna; Besset, Tatiana; Maes, Bert U. W.; Schnürch, Michael
Abstract : The present review is devoted to summarizing the recent advances (2015–2017) in the field of metal-catalysed group-directed C–H functionalisation. Abstract : The present review is devoted to summarizing the recent advances (2015–2017) in the field of metal-catalysed group-directed C–H functionalisation. In order to clearly showcase the molecular diversity that can now be accessed by means of directed C–H functionalisation, the whole is organized following the directing groups installed on a substrate. Its aim is to be a comprehensive reference work, where a specific directing group can be easily found, together with the transformations which have been carried out with it. Hence, the primary format of this review is schemes accompanied with a concise explanatory text, in which the directing groups are ordered in sections according to their chemical structure. The schemes feature typical substrates used, the products obtained as well as the required reaction conditions. Importantly, each example is commented on with respect to the most important positive features and drawbacks, on aspects such as selectivity, substrate scope, reaction conditions, directing group removal, and greenness. The targeted readership are both experts in the field of C–H functionalisation chemistry (to provide a comprehensive overview of the progress made in the last years) and, even more so, all organic chemists who want to introduce the C–H functionalisation way of thinking for a design of straightforward, efficient and step-economic synthetic routes towards molecules of interest to them. Accordingly, this review should be of particular interest also for scientists from industrial R&D sector. Hence, the overall goal of this review is to promote the application of C–H functionalisation reactions outside the research groups dedicated to method development and establishing it as a valuable reaction archetype in contemporary R&D, comparable to the role cross-coupling reactions play to date.